Effective design of Load Frequency Controller for a Single Area System using Sailfish Optimization Algorithm - Sambariya, Shuhangi; Lalwani, M.; Sambariya, D. K. (2025 4th OPJU International Technology Conference (OTCON) on Smart Computing for Innovation and Advancement in Industry 5.0, 2025)
This paper presents a load-frequency control (LFC) strategy for a single-area power system, utilizing a proportional-integral-derivative (PID) controller optimized through the Sailfish Optimization Algorithm (SFO). The PID controller parameters are fine-tuned using the integral square error (ISE) of the frequency deviation as the objective function during the optimization process. The system's frequency response is evaluated under three scenarios: without a controller, with a controller from the literature, and with the proposed SFO-PID controller. Performance metrics, including rise time, settling time, peak time, and undershoot, are analyzed to compare the step response in each case. Results indicate that the proposed SFO-PID controller significantly improves system performance, achieving faster and more stable frequency regulation, thereby demonstrating its efficacy for LFC in power systems.